Cenografia e ethos discursivo em o artigo do mestre Masaharu Taniguchi - Fernandes, Claudia Silva (2013)
This study is based on the postulates by the French line of the Theory of Disiscourse and has as theme the examination of the scenography as well as the discourse ethos in the process of revelation of the enunciator subject in Master Masaharu Taniguchi's Article, published in Seicho-No-Ie s Pomba Branca (White Dove) magazine. Such theme proves to be relevant, since we aimed at understanding the way how subjects interact in a discourse used for the propagation and maintenance of institutional values and concepts. For this purpose, we elected as basis Dominique s Maingueneau approach on interdiscourse, enunciative scene and discoursive ethos. The carried out investigation deals with a theoretical analytical procedure in which we analyze the enunciative scene, in its tripartition in englobing scene, generic and scenography as well as the form of unveiling of the discoursive ethos. Our study emphasized the role of interdiscoursivity in the organization of Seicho-No-Ie s discourse, especially the crossing of the discoursive fields of religiosity, pedagogical and scientific ones, among others, as well as the fact that the image constructed by the enunciator subject is the one of a master who acts in the scenery of a classroom with the target of achieving the adhesion of the coenunciator